H+‐pyrophosphatase IbVP1 promotes efficient iron use in sweet potato [Ipomoea batatas (L.) Lam.]. Issue 6 (10th February 2017) - Fan, Weijuan; Wang, Hongxia; Wu, Yinliang; Yang, Nan; Yang, Jun; Zhang, Peng
Summary: Iron (Fe) deficiency is one of the most common micronutrient deficiencies limiting crop production globally, especially in arid regions because of decreased availability of iron in alkaline soils. Sweet potato [ Ipomoea batatas (L.) Lam.] grows well in arid regions and is tolerant to Fe deficiency. Here, we report that the transcription of type I H + ‐pyrophosphatase (H + ‐PPase) gene IbVP1 in sweet potato plants was strongly induced by Fe deficiency and auxin in hydroponics, improving Fe acquisition via increased rhizosphere acidification and auxin regulation. When overexpressed, transgenic plants show higher pyrophosphate hydrolysis and plasma membrane H + ‐ATPase activity compared with the wild type, leading to increased rhizosphere acidification. The IbVP1 ‐overexpressing plants showed better growth, including enlarged root systems, under Fe‐sufficient or Fe‐deficient conditions. Increased ferric precipitation and ferric chelate reductase activity in the roots of transgenic lines indicate improved iron uptake, which is also confirmed by increased Fe content and up‐regulation of Fe uptake genes, e.g. FRO2, IRT1 and FIT . Carbohydrate metabolism is significantly affected in the transgenic lines, showing increased sugar and starch content associated with the increased expression of AGPase and SUT1 genes and the decrease in β‐amylase gene expression. Improved antioxidant capacities were also detected in the transgenic plants, which showed reduced H2 O2 accumulation associated with up‐regulated ROS‐scavenging activity. Therefore, H + ‐PPase plays a key role in the response to Fe deficiency by sweet potato and effectively improves the Fe acquisition by overexpressing IbVP1 in crops cultivated in micronutrient‐deficient soils.